The Impact of AirAsia’s E-Commerce Websites on Its Consumer Buying Behavior - Singh, Padmalini; D, Dilip.; Wen, Goh Kai; Kee, Daisy Mui Hung; Yee, Go Sin; Ying, Lee Chiew; Ling, Fong Kai; Shammas, Mohammed; Tandra, Gerald Reynaldo; Sin, Liem Gai (AIBPM Publisher, 2021)
The purpose of this study is to examine the impact of e-commerce websites on consumer’s buying behavior of AirAsia and to provide suggestions to AirAsia to improve its consumer’s shopping experience on its e-commerce website. This research applied qualitative methodology by interviews. It will provide the company with additional understanding about the impact of e-commerce websites on consumer’s buying behavior and the effective suggestions provided are highly practicable for the company. It is necessary for AirAsia to understand their consumer’s buying behavior to improve the company’s performance. Thus, AirAsia needs to put some effort into the research of consumer’s buying behavior and constantly improve its consumer’s shopping experience.